MENINGKATKAN KEPATUHAN DAN PENERIMAAN PAJAK MELALUI WITHHOLDING TAX SYSTEM - I Nyoman Darmayasa; Yuyung Rizka Aneswari; Elana Era Yusdita (Universitas Trunojoyo Madura, 2016)
The research aimed to understand deeply about withholding tax system in Indonesia and propose taxation strategy to maximize withholding tax according to self assessment system. The research use interpretive paradigm with literature method approach. The result of the research indicate that first, tax compliance in Indonesia is still low category so it need efforts to improve. Second, with withholding tax system will assurance due tax payment because tax taker is more discipline to cut tax for tax payer. Third, withholding tax system can control effectively and efficiently to minimize examination object not for personal tax payer but for work or income giver. Fourth, through the withholding tax system, tax payers would cut taxes when the conditions of high economic capacity. Fifth, several proposals to improve the maximization WHT include expanding the tax base and direct tax cuts were not final is still possible into the final tax in the scheme of withholding tax, giving rewards to a third party who is disciplined and obedient, open access to the Direktorat Jenderal Pajak (DJP) on the banks of the effectiveness of tax policy and make the Single Identification Number (SIN) to attract new taxpayers. This study contributes to the formulation of policies Direktorat Jenderal Pajak (DJP).